THE ROLE OF COOPERATIVES IN THE ECONOMIC DEVELOPMENT OF COOPERATIVE MEMBERS IN TUBAN DISTRICT - Geraldie Makruf Nugroho Kusuma (Universitas 17 Agustus 1945 Surabaya, 2023)
This research is a qualitative descriptive study. The subject of this research is the field of cooperatives at the Office of Cooperatives for Small and Medium Enterprises and Trade in Tuban Regency and cooperative actors. The research instrument is the researcher himself. Data collection techniques used are observation, interview, and documentation techniques. The data analysis technique used is data reduction, data display, and conclusion or verification. The theory used in this study uses the opinion put forward by Soerjono Soekanto which consists of a formal role, an informal role, an active role, and a participatory role. Based on the research, it can be concluded that the formal role of cooperatives as providers is part of supporting capital and formal institutions that provide for the needs of cooperative members and the general public, the informal role of cooperatives is an implicit (emotional) role, so when many members actively save, pay contributions, then the turnover of cooperative funds becomes smooth, the active role of cooperatives is holding annual meetings with members or RAT, the passive role of cooperatives is that there are no activities such as Annual Member Meetings so there are no reports to Diskopumdag and participatory roles are when cooperatives and their members both understand their roles and working together to advance the cooperative. It can be seen that the role of cooperatives is very important in helping the community's economy, especially those who are members of cooperatives, so the existence of cooperatives, both active and inactive, needs to be encouraged and facilitated to develop the quality of cooperative management so that the existence of cooperatives can help the economic development of the community, especially to encourage improvement the economy and welfare of its members.